Antropologi Biologi di Indonesia: Sebuah Penelusuran dan Kemungkinan Pengembangan - Iman Fachruliansyah (Antropologi Indonesia, 2018)
Indonesia has a great diversity of ethnic groups, languages, physical characteristics, and human genetic structures. Various studies of human physical variation and their evolutionary history in the world have received substantial contributions from biological anthropology researches in Indonesia. However, biological anthropology studies in Indonesia are not established or less familiar even among Indonesian anthropology milieu. This condition is reflected in a small numbers of Indonesian biological anthropologists, despite the vision of the founders of Indonesian anthropology that programmed the development of biological anthropology as a part of the anthropology department. This article aims to review the history of biological anthropology studies in Indonesia. Therefore, as a preliminary note, considerable scientific publications in biological anthropology in Indonesia will be discussed briefly to demonstrate the development of Indonesian biological anthropology.